RECONSTRUCTING A NUSANTARA SPIRITUAL MENTAL HEALTH MODEL: A COMPARATIVE STUDY OF SANGHYANG SIKSA KANDANG KARESIAN, SEWAKA DARMA, AND AL-GHAZALI’S IHYA’ ULUM AL-DIN - naan naan; Yogi Supriyadi; Didi Supandi (ILMU USHULUDDIN, 2026)
Studies of Olf Sundanese manuscripts have predominantly focused on philological, historical, and linguistic aspects, leaving their spiritual and therapeutic dimensions largerly unexsplored in dialogue with Islamic intellectual traditions. This article investigates the concept of mental health in Sanghyang Siksa Kandang Karesian (SSKK) and Sewaka Darma (SD) through Pierre Hadot's notion of philosophy as a way of life and compares it with Abu Hamid al-Ghazali's concept of tazkiyat  al-nafs in Ihya' Ulum al-Din. Position at the intersection of indigenous spirituality, Islamic theology, and contemporary mental health discourse, the study employs a qualitative library-based method with a philosophical hermeneutic aproach. The analysis focuses on the concepts of Dasa Kreta, Catur Yatna, Dasamala, Bayu-Sabda-Hedap, as well as riyadah al-nafs, mujahadah, muraqabah, and tazkiyah in Al-Ghazali's thought. The findings demonstrate that the three texts share a common structure of spiritual transformation consisting of self-regulation, purification of the soul, and existential trancendence. Dasa Kreta function similarly to Al-Ghazali's mujahadah al-nafs, as a mechanismof ethical self-discipline, while Dasamala parallels the concept of spiritual deaseas requiring purification. Furthermore, Jatiniskala and ma'rifatullah represent the highest stage of spiritual realization. This article proposes a conceptual model of nusantara  spiritual mental health that integrates Old Sundanese wisdom, Islamic Sufisme, and Hadot's Theeory of spiritual execises.